Foreseeability as an Element of Fundamental Breach Under the Un Convention On Contracts for The International Sale of Goods - 1980 (Al-Mukhtar Journal of Legal Science, 2024)
The aim of this study is to address two daunting problems. The first problem is identifying the concept of foreseeability, and the second daunting problem is identifying the importance and the time requirement of foreseeability. This study will be relied on both analytical and critical methods. The core of the analysis will be on the prospective of the UN Convention-1980 for foreseeability, as an element of fundamental breach in international sale of goods.
Keywords: Fundamental Breach; Foreseeability; International Sale of Goods; Time Requirement of Foreseeability